Profit Effects of Consumers’ Identity Management: A Dynamic Model - Laussel, Didier; Van Long, Ngo; Resende, Joana (Management Science, 2023)
We consider a nondurable good monopolist that collects data on its customers in order to profile them and subsequently practice price discrimination on returning customers. The monopolist’s price discrimination scheme is leaky in the sense that an endogenous fraction of consumers choose to incur a privacy cost to conceal their identity when they return in the following periods. We characterize the Markov perfect equilibrium of the game under two alternative customer profiling regimes: full information acquisition (FIA) and purchase history information (PHI). In both cases, we find that, contrary to what could be expected, the monopolist’s aggregate profit is not monotonically increasing in the level of the privacy cost, but a U-shaped function of it, leading to ambiguous profit effects: a reduction in privacy costs increases the fraction of customers who choose to be anonymous (detrimental profit effect), but it also softens the firm’s introductory price, reducing the pace at which prices targeted to new customers fall over time (positive profit effect). When comparing results under FIA and PHI, we find that market expansion is faster, and more customers conceal their identity under FIA than under PHI. Equilibrium profits are also higher in the FIA case. Although equilibrium profits are U-shaped functions of the privacy cost in both profiling regimes, they tend to be globally decreasing with the privacy cost under PHI and globally increasing under FIA. This paper was accepted by Eric Anderson, marketing. Funding: This work was supported by Fundação para a Ciência e a Tecnologia [Grants NORTE-01-0145-FEDER-028540 and POCI-01-0145-FEDER-006890]. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2022.4511 .